Evolution of the Correa's cascade steps: A long-term endoscopic surveillance among non-ulcer dyspepsia and gastric ulcer after H. pylori eradication - Cheng, Hsiu-Chi; Yang, Yao-Jong; Yang, Hsiao-Bai; Tsai, Yu-Ching; Chang, Wei-Lun; Wu, Chung-Tai; Kuo, Hsin-Yu; Yu, Yu-Ting; Yang, Er-Hsiang; Cheng, Wei-Chun; Chen, Wei-Ying; Sheu, Bor-Shyang (Journal of the Formosan Medical Association, 2023)
This study is aimed toward investigating the evolution of each Correa's step after Helicobacter pylori eradication in a long-term follow-up and exploring the factors correlated with a high-risk of gastric cancer. A total of 1824 H. pylori-infected subjects were enrolled to receive screening endoscopy. Among them, 491 received surveillance endoscopy. The patients were divided into Correa's steps I to VI, from normal to gastric cancer. A group-based trajectory model was used to classify patients as persistent high-risk status or not. The prevalence rates of positive corpus-predominant gastritis index (CGI) were 20%–40% in all age groups and Correa's steps IV-V increased >35% after 50 years based on screening endoscopy. Successful eradication of H. pylori regressed CGI after the 1st year-and-thereafter (P < 0.05) and decreased Correa's step progression (Relative risk 0.66 [95% CI 0.49–0.89], P = 0.01); however, it did not regress OLGA and OLGIM. Not only in steps IV-V, but also in step III, the patients had a risk of developing gastric cancer (11.13–76.41 and 4.61 per 1000 person-years). Age (Hazard ratio 1.012 [1.003–1.020], P = 0.01), OLGA stages ≥ I (2.127 [1.558–2.903], P < 0.001), and OLGIM stages ≥ I (1.409 [1.119–1.774], P = 0.004) were correlated independently with a persistent high-risk status. The patients in Correa's steps III-V, but not I-II, were at risk of gastric cancer after H. pylori eradication. Age, OLGA stages ≥ I, and OLGIM stages ≥ I were independent factors correlated to a persistent high-risk of gastric cancer. The data may be useful when scheduling surveillance endoscopy for subjects in each Correa's step (NCT04527055).